2007
DOI: 10.2190/iq.27.1.e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Support, Hardiness, and Acculturation as Predictors of Mental Health among International Students of Asian Indian Origin

Abstract: This study determined the role of social support, hardiness, and acculturation as predictors of mental health among international Asian Indian students enrolled at two large public universities in Ohio. A sample of 185 students completed a 75-item online instrument assessing their social support levels, acculturation, hardiness, and their mental health. Regression analyses were conducted to test for variance in mental health attributable to each of the three independent variables. The final regression model re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 24 publications
(26 reference statements)
4
46
0
Order By: Relevance
“…These findings are consistent with studies demonstrating a negative association between social support and psychological distress (including acculturative stress, depression, and anxiety) (Dao, et al, 2007;Poyrazli, et al, 2004;Sumer, et al, 2008;J. Zhang & Goodson, 2011); and a positive association with psychological well-being (Atri, et al, 2006). In contrast, a study of 74 Korean international students in the U.S.A found that social support did not have a direct effect on international students' mental health symptoms (J.-S. Lee, et al, 2004).…”
Section: Acculturative Stress Of International Studentssupporting
confidence: 88%
“…These findings are consistent with studies demonstrating a negative association between social support and psychological distress (including acculturative stress, depression, and anxiety) (Dao, et al, 2007;Poyrazli, et al, 2004;Sumer, et al, 2008;J. Zhang & Goodson, 2011); and a positive association with psychological well-being (Atri, et al, 2006). In contrast, a study of 74 Korean international students in the U.S.A found that social support did not have a direct effect on international students' mental health symptoms (J.-S. Lee, et al, 2004).…”
Section: Acculturative Stress Of International Studentssupporting
confidence: 88%
“…This may be because the availability of stable jobs fulfilled migrant nurses' initial intentions to migrate (Atri et al . , Kingma , Djukic et al . ).…”
Section: Discussion and Implications For Nursing Managementmentioning
confidence: 97%
“…Overall, the study found that the job satisfaction level of migrant nurses was high. This may be because the availability of stable jobs fulfilled migrant nurses' initial intentions to migrate (Atri et al 2006, Kingma 2008, Djukic et al 2010. Compared with Filipino, Malaysian and Indian migrant nurses, Chinese migrant nurses had the lowest levels of job satisfaction.…”
Section: Discussion and Implications For Nursing Managementmentioning
confidence: 99%
“…Additionally, reported that greater familial and graduate social support reduced international students' stress level. Atri, Sharma, and Cottrell (2007) found in their study that one type of social support, namely, emotional support, was significantly related to sojourners' mental health. Relatedly, findings from Dao et al (2007) indicated that "Taiwanese international students who were at risk of depressive feelings were more likely to be those who had the perception of limited social support" (p. 287).…”
Section: Social Supportmentioning
confidence: 96%